« Un vif sentiment de plaisir » L’art de vivre à la marocaine selon Eugène Delacroix et Tahar Ben Jelloun - Sokołowicz, Małgorzata (L’art de vivre, de survivre, de revivre. Approches littéraires. Le 50e anniversaire des études romanes à l’Université de Łódź, 2022)
The present paper focuses on the travel of Eugène Delacroix to Morocco (firstsix months of 1832) and his accounts given in his travel notes, letters and an unfinishedtravelogue, Souvenirs d’un voyage dans le Maroc. The writings of the famous painter arecontrasted with the book by a Moroccan writer, Tahar Ben Jelloun, Lettre à Delacroix (2005).The aim of the paper is to define the art of living à la marocaine according to the French painterand the Moroccan writer. It is done in three parts. The first one is devoted to the beautyof Moroccan landscapes, horses and architecture. The second focuses on the art of dressing:the beauty of the inhabitants of the country and the elegance of their cloths. The last partdiscusses Moroccan traditions, based – according to Delacroix – on Antiquity.